-11p+1=-8p-3p

Simple and best practice solution for -11p+1=-8p-3p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11p+1=-8p-3p equation:



-11p+1=-8p-3p
We move all terms to the left:
-11p+1-(-8p-3p)=0
We add all the numbers together, and all the variables
-11p-(-11p)+1=0
We get rid of parentheses
-11p+11p+1=0
We add all the numbers together, and all the variables
1!=0
There is no solution for this equation

See similar equations:

| -7(f-8=-11 | | x/22=9=12 | | 9x+5=11x+13 | | 37.02=7g+3.98 | | 2h+7=25 | | −5r−1=−1 | | -4x=-4x+7 | | -5+6a-2-4=4a+5 | | -6-6f=3-7f | | 9x-17=x+15 | | 6x+2=2+10 | | 12+20/x=20 | | 9+5a=2a | | 7/8w=3/8 | | 5-m=-9+7+6m | | 4-n=4-7n-3n | | 201=96-w | | x–(–4)=20 | | x-2+x+x+2=72 | | -2+7u=4+4u | | 2.7z-3.5z=6 | | 2x+7x=-45 | | 4(2w+3)-7=9 | | 12-2y=-4 | | -9y-4y=-39 | | X+6=2x+-10 | | 8x+8=10x-10 | | 8-x/7=-32 | | 15x-24=8x+25 | | -9y-4=-7y+10 | | 5-x=-32 | | x+9=x4=120 |

Equations solver categories